2005
DOI: 10.1111/j.1365-2672.2004.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of viruses on fresh produce, using MS2 as a surrogate for norovirus

Abstract: Aims: To study the survival and removal of viruses from fresh fruit and vegetables using the bacteriophage MS2 as a potential surrogate for noroviruses. Method and Results: Survival of MS2 in buffer and on fresh produce was studied at 4, 8 and 22°C. At 4 and 8°C a reduction of <1 log 10 was observed after 50 days in buffer; however a reduction in excess of 1 log 10 occurred within 9 days at 22°C. Similar results were obtained with fresh produce with virus survival times exceeding the shelf life of the produce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
119
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 19 publications
2
119
1
Order By: Relevance
“…In this study, bacteriophage MS2 was shown to survive for prolonged periods (10 days) on FFRs at 22°C and 30% RH. These results are not unexpected as Dawson et al (2005) demonstrated survival of MS2 virus on vegetable produce and in buffered solution for 43 and 50 days, respectively, with both tests conducted at 22°C.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In this study, bacteriophage MS2 was shown to survive for prolonged periods (10 days) on FFRs at 22°C and 30% RH. These results are not unexpected as Dawson et al (2005) demonstrated survival of MS2 virus on vegetable produce and in buffered solution for 43 and 50 days, respectively, with both tests conducted at 22°C.…”
Section: Discussionsupporting
confidence: 48%
“…The persistence of microbes on environmental surfaces is dependent upon a multitude of factors such as the type of microorganism, temperature and humidity conditions, microbe-associated organic and inorganic residues, as well as the physical properties of the fomite (Abad, Pinto, & Bosch, 1994;Bean et al, 1982;Dawson et al, 2005;Kramer, Schwebke, & Kampf, 2006;Tiwari et al, 2006). In this study, bacteriophage MS2 was shown to survive for prolonged periods (10 days) on FFRs at 22°C and 30% RH.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteriophage MS2 is a virus commonly used as a surrogate for human viruses in disinfection studies because of its physicochemical similarities to common pathogenic viruses (e.g., size and shape), the similarity of its behavior in various treatment processes to mammalian viruses, and the relative ease with which it can be studied. 35 Finally, we chose to use murine norovirus (MNV) in our SODIS studies because it is the best current surrogate for human norovirus, which cannot be cultured under laboratory conditions. 36 The effect of SODIS on viruses has not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, any type of food product is a potential vehicle for NoV transmission and can cause infection with only a few infectious NoV particles (7). However, the consumption of fresh produce and ready-to-eat food contaminated by ill or asymptomatic food handlers has been identified as the most common source of NoV outbreaks (9,10,37).…”
mentioning
confidence: 99%
“…Due to the lack of animal models or suitable tissue culture, several studies have evaluated the persistence of human NoV using surrogates such as feline calicivirus (FCV) (11,40), MS2 phage (10), and more recently murine NoV (7) in various foodstuffs and environmental conditions. FCV is a respiratory pathogen that it is unstable under acidic and environmental conditions (7,15).…”
mentioning
confidence: 99%